Solid-phase extraction of active compounds from natural products by molecularly imprinted polymers: Synthesis and extraction parameters - Kamaruzaman, Sazlinda; Mohammad Nasir, Najihah; Mohd Faudzi, Siti Munirah; Yahaya, Noorfatimah; Mohamad Hanapi, Nor Suhaila; Wan Ibrahim, Wan Nazihah (MDPI AG, 2021)
Molecularly imprinted polymers (MIPs) are synthetic polymers with a predetermined selectivity for a particular analyte or group of structurally related compounds, making them ideal materials for separation processes. Hence, in sample preparation, MIPs are chosen as an excellent material to provide selectivity. Moreover, its use in solid-phase extraction, also referred to as molecular imprinted solid phase extraction (MISPE), is well regarded. In recent years, many papers have been published addressing the utilization of MIPs or MISPE as sorbents in natural product applications, such as synthesis. This review describes the synthesis and characterization of MIPs as a tool in natural product applications.